Is Business Risk Able to Moderate the Effect of Capital Intensity, Capital Structure, and Tax Loss Carryforward on the Effective Tax Rate? - Mardiansyah, Apri; Faried Arfiansyah, Mochammad; Murtanto, Murtanto (AKRUAL: Jurnal Akuntansi, 2025)
Research Backgrounds: The relevance of explaining the aspects that determine tax management procedures in manufacturing businesses that are listed on the IDX is the driving force behind the requirement of doing this research. Introduction/ Objectives: The purpose of this research is to investigate the impact that factors like as capital intensity, ownership structure, and tax loss carryforward have on the effective tax rate, with business risk serving as a moderating element in the analysis. Methods: The research method that was utilized was quantitative, and it had a positivistic approach. The PLS-SEM analytic methodology was utilized. The sample was comprised of 23 manufacturing businesses that were selected using the process of purposive sampling. These companies were listed on the IDX and were in the staples retailing and beverage sub-sector. Results: According to the findings, the effective tax rate is significantly impacted by company risk, ownership structure, and tax loss carryforward. On the other hand, capital intensity and moderating effect 3 do not have any impact on the effective tax rate. When it comes to tax planning, it may be advantageous for businesses to take into account the ownership structure and the risk of the firm. On the other hand, tax authorities may need to pay attention to businesses that use the tax loss carryforward in order to maximize their tax management. Conclusion: These findings offer valuable insights for practitioners and policymakers engaged in the formulation of more efficacious tax policies. Companies may wish to consider business risk and ownership structure in their tax planning, while tax authorities may be well advised to devote greater attention to firms that utilize tax loss carryforwards to optimize tax management.